From Wish to Reality: Soteria in Regular Care—Proof of Effectiveness of the Implementation of Soteria Elements in Acute Psychiatry - Wolf, Theresa; Fabel, Philine; Kraschewski, Adrian; Jockers-Scherübl, Maria C. (Frontiers in Psychiatry, 2021)
Objective: This article examines the influence of the implementation of Soteria- elements on coercive measures in an acute psychiatric ward after reconstruction in 2017, thereby comparing the year 2016 to the year 2019. The special feature is that this is the only acute psychiatric ward in Hennigsdorf Hospital, connected now both spatially and therapeutically to an open ward and focussing on the treatment of patients suffering from schizophrenia and schizophrenia spectrum disorders. Methods: The following parameters were examined: aggressive assaults, use of coercion (mechanical restraints), duration of treatment in open or locked ward, type of discharge, coercive medication, and dosage of applied antipsychotics. For this purpose, the data of all patients accommodated according to BbgPsychKG and BGB in the year 2016 (before the reconstruction) and 2019 (after the reconstruction) were statistically analyzed in a pre-post mirror quasi-experimental design. Results: In 2019, the criteria of the Soteria Fidelity Scale for a ward with Soteria- elements were reached. In comparison to 2016 with a comparable care situation and a comparable patient clientele, there was now a significant decrease in aggressive attacks on staff and fellow patients, a significantly reduced number of fixations, a significantly reduced overall duration of inpatient stay and a significant increase in treatment time in the open area of our acute ward. Conclusion: The establishment of Soteria- elements in the acute psychiatric ward leads to a verifiable less violent environment of care for severely ill patients and to a drastic reduction in coercive measures.